Separation and identification of microfibers in the wastewaters of textile finishing process - AKYILDIZ, SİNEM HAZAL; YALÇIN, BAHATTİN (My University, 2023)
Microplastic pollution is a major global issue, with the textile industry responsible for 35% of the microplastics (MPs) released as microfibers (MFs). Due to their small size, MPs can interact with a wide range of organisms and lead to chromosomal mutations that cause obstruction, inflammation, and organ accumulation. This study aims to detect and separate MFs released from the textile finishing machinery, which is used to give a soft touch to fabrics. Before being transferred to the effluent water, the wastewater samples taken from the section were pretreated with 15% H2O2at 25 °C for 5 days, and thenMFs were captured by a filter. Filters with accumulated MFs were observed using a light microscope, and a micro-FTIR was used to detect MFs chemically. The main results showed that acrylic and cotton MFs were detected in wastewater, and wastewater samples from different dates contained0.058 g/L and 0.251 g/LMFs which reveals the seriousness of the MP problem we are facing.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES